2013
DOI: 10.1002/ccd.25264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of coronary chronic total occlusions in a tertiary veterans affairs hospital

Abstract: Objectives We sought to determine the contemporary prevalence and management of coronary chronic total occlusions (CTO) in a veteran population. Background The prevalence and management of CTOs in various populations has received limited study. Methods We collected clinical and angiographic data in consecutive patients that underwent coronary angiography at our institution between January 2011 and December 2012. Coronary artery disease (CAD) was defined as ≥50% diameter stenosis in ≥1 coronary artery. CTO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(114 citation statements)
references
References 19 publications
(25 reference statements)
3
106
0
5
Order By: Relevance
“…CTOs have received this attention because they are prevalent among patients with coronary artery disease [1][2][3][4][5] and are present in as many as 10% to 20% of all patients referred for diagnostic angiography. 6,7 However, PCI success rates for CTO have been demonstrated in earlier studies to be only in the 60% to 70% range, 8 although some centers have reported success rates >80%.…”
mentioning
confidence: 99%
“…CTOs have received this attention because they are prevalent among patients with coronary artery disease [1][2][3][4][5] and are present in as many as 10% to 20% of all patients referred for diagnostic angiography. 6,7 However, PCI success rates for CTO have been demonstrated in earlier studies to be only in the 60% to 70% range, 8 although some centers have reported success rates >80%.…”
mentioning
confidence: 99%
“…22 Similar distributions of CTOs have been reported by other investigators. 2,4,[22][23][24] The anatomic location of CTOs within each coronary artery can be either the proximal/mid segment or at the mid/distal segment. This may have treatment implications because PCI procedures are in the majority of cases not suitable for distal coronary segments (hence are not able to treat distal CTOs), whereas CABG procedures are generally performed in distal coronary segments and hence are able to treat both proximal and distal CTOs (Figure 1).…”
Section: Coronary Anatomic Variability Of Ctosmentioning
confidence: 99%
“…1 They are commonly found in patients with coronary artery disease undergoing coronary angiography (13.3%-52%). [2][3][4][5][6] Percutaneous coronary intervention (PCI) of a CTO is traditionally considered a procedure with low success and high complication rates, ''a temptation to be avoided.'' Significant improvements, however, have been achieved in recent years resulting in high success rates by several expert operators and centers.…”
Section: N Introductionmentioning
confidence: 99%